Academic article: an intercultural academic practice? - Killner, Mariana; Jung, Neiva Maria (BELT - Brazilian English Language Teaching Journal, 2019)
In Brazilian universities, some policies resulting from globalization processes, among them the internationalization of Higher Education, have resulted in other public policies on the implementation of these policies. Although there is a worldwide academic policy that favors the monopoly of English, according to Hamel (2013), foreign students in Brazilian universities face the challenges of the Brazilian academic literacy. Thus, in order to contribute to these policies, especially the internationalization of universities, Killner and Furtoso (2016) developed material for foreign postgraduate students. This material constitutes a Didactic Manual for the teaching of PFL in academic context and is composed of four Didactic Units (Summary, Review, Oral Presentation and Academic Article). In this context, we aim to develop understandings about the didactic unit referring to the genre academic article. We understand that there are literacies related to social, cultural and ideological contexts, rather than a single, neutral literacy (Street, 1984, 1993, 2014; Street; Lefstein, 2007).